2005
DOI: 10.1111/j.1654-1103.2005.tb02406.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of dipterocarps during low intensity masting events in a Bornean rain forest

Abstract: Question: The evolution of general flowering and mast fruiting of dipterocarps in tropical rain forest has been explained by different mechanisms. We studied whether the abundance of flowering conspecifics influences the recruitment success of tropical forest trees in Borneo. Location: Sepilok Forest Reserve, Sabah, Malaysia. Method: We examined the recruitment success of 17 species of Dipterocarpaceae in a 640–ha sample area over two flowering events in 2001–2002 using seed traps and quadrats. Seed predation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 34 publications
(52 reference statements)
2
59
1
1
Order By: Relevance
“…Emergence rates from seeds kept in the laboratory provide a more realistic estimate of invertebrate attack. In the absence of vertebrate predators, insects attacked about 9 per cent of seeds, low in comparison with other studies from the region [25,51]. However, even our laboratory data will probably underestimate insect predation.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Emergence rates from seeds kept in the laboratory provide a more realistic estimate of invertebrate attack. In the absence of vertebrate predators, insects attacked about 9 per cent of seeds, low in comparison with other studies from the region [25,51]. However, even our laboratory data will probably underestimate insect predation.…”
Section: Discussioncontrasting
confidence: 72%
“…However, Maycock et al [25] also reported negligible survival of other dipterocarp species in the same fruiting event. One possible explanation could be that P. malaanonan seeds are unpalatable.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hence the number of surviving seeds is a direct function of the number of seeds produced over the ''satiation threshold,'' that is the number of seeds required to satiate seed predators. For large obligately outcrossed and animal-pollinated plants, however, an upper limit on seed production is likely to be imposed by pollinator limitation, which is expected to be severe under the circumstances of mast flowering (Maycock et al 2005). Thus, when the percentage of mature seeds predated by insects or vertebrates prior to dispersal approaches 100%, and in dipterocarps it frequently exceeds 50% (Toy 1991, Nakagawa et al 2005, it seems highly advantageous to increase seed production over the satiation threshold as every seed over this threshold will escape predation.…”
Section: A Hypothesismentioning
confidence: 99%
“…2d, f) may suggest asymptotic or unimodal relationships rather than linearly increasing ones between tree size and these fecundity parameters. Some external factors such as a lack of cross pollination (Ghazoul et al 1998) and seed consumption by insects and mammals (Chan 1980;Momose et al 1996;Nakagawa et al 2005;Maycock et al 2005) have been reported as being closely related to the pre-dispersal mortality of seeds in various dipterocarp species. However, the relationships between tree size and mature seed production Fig.…”
Section: Relationship Between Tree Size and Fecunditymentioning
confidence: 99%